The SAS programmer's PROC REPORT handbook basic to advanced reporting techniques - Eslinger, Jane (SAS Institute, 2016)
Whether you work in banking/finance, pharmaceuticals, the health and life sciences, or government, this unique book is intended for programmers of all skill levels and will help you harness all the power and capability of PROC REPORT. --
Includes bibliographical references and index. - Description based on online resource; title from title page (Safari, viewed April 27, 2016)
Keywords: SAS (Computer file); SAS (Computer file) -- Handbooks, manuals, etc; SAS (Computer program language) -- Handbooks, manuals, etc; SAS (Langage de programmation); Guides, manuels, etc; COMPUTERS / Computer Literacy; COMPUTERS / Computer Science; COMPUTERS / Data Processing; COMPUTERS / Hardware / General; COMPUTERS / Information Technology; COMPUTERS / Machine Theory; COMPUTERS / Reference; SAS (Computer program language); Handbooks and manuals